Effect of Calcium Carbonate Encapsulation on the Activity of Orally Administered CpG Oligonucleotides - Neslihan Kayraklioglu; Julia Scheiermann; W. Gregory Alvord; Dennis M. Klinman (Elsevier, 2017)
Synthetic oligodeoxynucleotides containing unmethylated CpG motifs (CpG ODNs) stimulate immune cells via Toll-like receptor 9 (TLR9). Because oligodeoxynucleotides (ODNs) are susceptible to gastric degradation, clinical trials designed to evaluate their therapeutic utility have relied solely on parenteral routes of administration. A strategy to improve the activity of orally delivered ODNs by reducing their susceptibility to gastrointestinal (GI) digestion via encapsulation in calcium carbonate nanoparticles (ODNcaps) was recently described. This study compares the in vitro and in vivo activity of encapsulated (ODNcaps) versus free CpG ODNs delivered orally or parenterally. ODNcaps mirrored the ability of free ODNs to stimulate splenic B cells and macrophages in vitro. ODNcaps activated immune cells in the Peyer's patches and mesenteric lymph nodes after oral delivery. Their effect on GI immunity was evaluated in studies of dextran sulfate sodium (DSS)-induced colitis and enteric infection, whereas systemic immunity was examined by monitoring their effect on lipopolysaccharide (LPS)-induced cytokine production and systemic pathogen challenge. Results indicate that orally delivered CpG ODNs predominantly induce GI rather than systemic immunity, and that calcium carbonate encapsulation does not significantly alter this behavior. Keywords: TLR9 agonist, delivery, activation, oral, encapsulated